Augmentation of HIV-specific T cell function by immediate treatment of hyperacute HIV-1 infection - Ndhlovu, Zaza M; Kazer, Samuel W; Nkosi, Thandeka; Ogunshola, Funsho; Muema, Daniel M; Anmole, Gursev; Swann, Shayda A; Moodley, Amber; Dong, Krista; Reddy, Tarylee; Brockman, Mark A; Shalek, Alex K; et al. (Science translational medicine, 2019)
Sustained viremia after acute HIV infection is associated with profound CD4 T cell loss and exhaustion of HIV-specific CD8 T cell responses. To determine the impact of combination antiretroviral therapy (cART) on these processes, we examined the evolution of immune responses in acutely infected individuals initiating treatment before peak viremia. Immediate treatment of Fiebig stages I and II infection led to a rapid decline in viral load and diminished magnitude of HIV-specific (tetramer ) CD8 T cell responses compared to untreated donors. There was a strong positive correlation between cumulative viral antigen exposure before full cART-induced suppression and immune responses measured by MHC class I tetramers, IFN-γ ELISPOT, and CD8 T cell activation. HIV-specific CD8 T responses of early treated individuals were characterized by increased CD127 and BCL-2 expression, greater in vitro IFN-γ secretion, and enhanced differentiation into effector memory (T ) cells. Transcriptional analysis of tetramer CD8 T cells from treated persons revealed reduced expression of genes associated with activation and apoptosis, with concurrent up-regulation of prosurvival genes including , , and Early treatment also resulted in robust HIV-specific CD4 T cell responses compared to untreated HIV-infected individuals. Our data show that limiting acute viremia results in enhanced functionality of HIV-specific CD4 and CD8 T cells, preserving key antiviral properties of these cells.